Sepsis in cougar (Puma concolor) associated with Chromobacterium violaceum - Mesquita, Mayara C. S. R. (Braz J Microbiol, 2021)
The genus Chromobacterium is widely distributed in the environment and is composed of Gram-negative, aerobic, or facultative anaerobic bacilli that occur in violet-colored colonies. These bacteria rarely cause infections, but when it occurs, it spreads quickly and has a high mortality. Because diseases are infrequent, the diagnosis is often delayed, and it takes time for suitable treatment to be initiated, leading to increased mortality due to the rapid progression of the disease. After the death of a cougar, serologically positive for feline leukemia virus, at the Center for Medicine and Research on Wild Animals of the Federal University of Mato Grosso, an autopsy was carried out, and fragments of its organs were sent for bacterial culture. Significant lesions were found, mainly in the liver and lungs, and upon bacterial isolation, violet-colored colonies were obtained from all of the referred organs, suggestive of C. violaceum, which was later confirmed by 16S DNA sequencing. The objective of this study was to report a case of death associated primarily with disseminated infection caused by C. violaceum in a FeLV-positive wild cougar in July 2018; no other occurrence in this species has yet been described. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s42770-021-00460-z.